Shear modulus and strength of an acrylic adhesive by the notched plate shear method (Arcan) and the thick adherend shear test (TAST) - Pinto, A. M. G. (2014)
In this work, the shear modulus and strength of the acrylic adhesive 3M® DP 8005 was evaluated by two different methods: the Thick Adherend Shear Test (TAST) and the Notched Plate Shear Method (Arcan). However, TAST standards advise the use of a special extensometer attached to the specimen, which requires a very experienced technician. In the present study, the adhesive shear displacement for the TAST was measured using an optical technique, and also with a conventional inductive extensometer of 25 mm used for tensile tests. This allowed for an assessment of suitability of using a conventional extensometer to measure this parameter. Since the results obtained by the two techniques are identical, it can be concluded that using a conventional extensometer is a valid option to obtain the shear modulus for the particular adhesive used. In the Arcan tests, the adhesive shear displacement was only measured using the optical technique. This work also aimed the comparison of shear modulus and strength obtained by the TAST and Arcan test methods.